2020
DOI: 10.1002/ijc.33360
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes and risk of endometrial cancer: A pooled analysis of individual participant data in the Epidemiology of Endometrial Cancer Consortium

Abstract: A full‐term pregnancy is associated with reduced endometrial cancer risk; however, whether the effect of additional pregnancies is independent of age at last pregnancy is unknown. The associations between other pregnancy‐related factors and endometrial cancer risk are less clear. We pooled individual participant data from 11 cohort and 19 case‐control studies participating in the Epidemiology of Endometrial Cancer Consortium (E2C2) including 16 986 women with endometrial cancer and 39 538 control women. We use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 35 publications
6
22
1
Order By: Relevance
“…Although the reduction of risk seen with cumulative time pregnant (>101 weeks) on cancer of the uterus was not statistically significant in this study, a recent analysis found that whilst there is a greater magnitude of reduction in risk for a full-term pregnancy than an early pregnancy loss, each additional pregnancy is associated with a further reduction in endometrial cancer risk [29].…”
Section: Discussioncontrasting
confidence: 86%
“…Although the reduction of risk seen with cumulative time pregnant (>101 weeks) on cancer of the uterus was not statistically significant in this study, a recent analysis found that whilst there is a greater magnitude of reduction in risk for a full-term pregnancy than an early pregnancy loss, each additional pregnancy is associated with a further reduction in endometrial cancer risk [29].…”
Section: Discussioncontrasting
confidence: 86%
“…This study is in line with a Danish study reporting no association between VB in pregnancy and occult cancer (21). The results of this study also indirectly support the findings of previous research showing that the risk of breast, ovarian and endometrial cancer was similar in women with a gestation history irrespective of whether the pregnancies were carried until full-term delivery (1,2,19).…”
Section: Comparison With Other Studiessupporting
confidence: 92%
“…Obesity causes excessive endogenous estrogen to act on the endometrium, leading to EH and EC. Studies [3,42,43] have shown that when the insulin resistance index is greater than or equal to 2.8809, the relative risks of endometrial hyperplasia and endometrial cancer are 35.22 and 30.59, respectively. It's been found that when BMI ≥ 25 kg/m 2 , progesterone treatment is less effective and prone to recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Endometrial cancer (EC) is one of the common malignant tumors in gynecology, and its incidence is increasing year by year, and is showing a trend of younger onset age [1]. It is generally believed that the continuous stimulation of estrogen without progesterone antagonism leads to endometrial hyperplasia and then cancerous transformation [2,3]. Endometrial hyperplasia (EH) is a common gynecological endocrine disease, which mainly manifests as irregular vaginal bleeding, infertility, and even malignant transformation [4].…”
Section: Introductionmentioning
confidence: 99%